Salary and Wages in Malaysia - Ghani, Rohayu; Arshad, Rashidah; Idris, Fazli; Othman, Rozhan; Halid, Noreha; Poon, June; Trisna, Ayu (Journal of Comparative International Management, 2001)
This paper discusses the compensation practices in Malaysia against the backdrop of the legal framework for wage and salary deterinatio n. It also exa mines the Malay sian labo ur mark et situation a nd trends in salary and wage administration together with the role of unions in compensation determination.